Consentimento e o direito à privacidade sob a ótica da lei geral de proteção de dados pessoais - Mihich, Alexandre Multini (2021)
Nowadays, the regulation of data protection becomes necessary, in view of the widespread collection of information. Countless daily actions include transactions involving personal data, such as the relationship between the employee and his employer or the relationship between the consumer and the supplier on the streaming platforms, and put the citizen at a disadvantage and even vulnerability. Thus, this dissertation intends to provide a critical analysis of the General Data Protection Law, in particular seeking to investigate whether the right to privacy is safeguarded by the law and, also, whether the consent of the data subject is well contemplated. Another objective outlined for this study is to clarify the importance and impact of the General Law for the Protection of Personal Data, which is understood to be superior to the Consumer Protection Code. There is no doubt that consumer law has changed the paradigms of relations between companies and natural persons. The methodology adopted in this work was the deductive one, starting from general arguments for particular arguments, having been presented the foundations that are considered true, in marked doctrine, to, then, arrive at particular formal conclusions, with the modest boldness of trying to establish bridges between ideas, thoughts and concepts in order to try a new approach on the topic. The research also makes critical considerations about the text of the General Law for the Protection of Personal Data in an inductive way, seeking to explain concepts and the normative nuances of certain devices that are relevant to the object of the research. Finally, the present study sought to demonstrate that consent has lost its central nucleus of protagonism, whether due to the dynamics of society or even the massification of data processing, and the enforcer of the law should revisit its concepts, especially the consent paradigm, so that use the other legal bases for processing personal data provided for in the General Personal Data Protection Law, such as legitimate interest or compliance with legal obligations.